El Desarrollo De Las Inteligencias Múltiples Como Estrategia De Enseñanza-Aprendizaje, De Las Estudiantes Del Cuarto Año De Educación General Básica De La Escuela Guayaquil, De La Parroquia San Juan Del Cantón Riobamba Provincia Del Chimborazo En El Año Lectivo 2010- 2011. - Morales Gavidia, Narcisa Mónica (2011)
This paper entitled "Development of Multiple Intelligences and Teaching-Learning Strategy of the seniors of General Basic Education School" Guayaquil "of the parish San Juan of the canton Riobamba Chimborazo Province in the school year 2010 -2011 "This research is done with the collection based on the seniors of basic general education and due confrontations with the results achieved in the respective test data applied. To meet this objective test be performed, both students and teachers and tossed results will be taken into count for the elaboration of the proposal with appropriate conclusions and recommendations thus achieving quality education. I put to your consideration the importance to be given to Development seven multiple intelligences in the students and the results of the analysis confirm the validity of the hypothesis proposed in this research. This thesis used methods sufficient to facilitate the process of the investigation. The aim of this paper is to present the process to follow to achieve in students the further development of each of the intelligences. Scientific information, it will serve me `Reference to overcome all kinds of difficulties students and possibly achieve the development of multiple intelligences is based on the theoretical framework. The development of multiple intelligences in humans allow navigate the world of science and technology and culture remembering the past and projecting a better future. This thesis was developed and operating activities was applied to overcome the difficulties in the seniors of Basic Education allowing better social psychological and intellectual development of each individual.